Konsep Was-Was dalam Perspektif Tafsir Ibn Katsir dan Relevansinya dengan Obsessive Compulsive Disorder (OCD) - Nursumayyah Damanik; Farid Adnir (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2026)
This study examines the concept of was-was according to Ibn Kathīr’s exegesis and its relevance to Obsessive-Compulsive Disorder (OCD) in modern psychology. Employing a library research method with a conceptual-comparative approach, this research analyzes the interpretation of Qur’anic verses on was-was in Tafsīr Ibn Kathīr and compares them with the clinical characteristics of OCD based on DSM-5 criteria and contemporary psychiatric literature. The findings reveal that was-was and OCD share phenomenological similarities, particularly in the manifestation of recurrent intrusive thoughts, pathological doubt, and compulsive behaviors performed as a response to anxiety. However, fundamental differences remain: was-was is understood as a spiritual whisper originating from satanic temptation that can be overcome through religious practices such as dhikr and isti‘ādhah, whereas OCD is classified as a neuropsychiatric disorder with specific diagnostic criteria, multifactorial etiology, and requires professional clinical intervention. This study concludes that OCD can be regarded as an extreme form of was-was that necessitates an integrative treatment approach combining psychotherapy, pharmacotherapy, and spiritual guidance. This research contributes to the interdisciplinary dialogue between Qur’anic exegesis and mental health studies.